Students' Responses to the Use of Educaplay in Integrated Science and Social Studies (IPAS) Learning among Fifth-Grade Elementary School Students - Salwa Az Zahrah; Trisni Handayani (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
Students' responses are an essential aspect of the learning process because they reflect how students perceive, understand, and engage with the learning experiences provided by teachers. However, limited variation in instructional methods often reduces students' participation and enthusiasm during classroom instruction. This study aimed to describe elementary school students' cognitive, affective, and conative responses to the use of Educaplay in Integrated Science and Social Studies (IPAS) instruction on the topic of the Earth's Layers. A descriptive qualitative approach was employed. Data were collected through classroom observations and semi-structured interviews involving six fifth-grade students, one classroom teacher, and one curriculum teacher. The data were analyzed using the Miles et al. interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that students demonstrated positive responses across the cognitive, affective, and conative dimensions. Cognitively, Educaplay supported students' conceptual understanding through visual representations and interactive quiz activities. Affectively, students showed greater enthusiasm, interest, and emotional engagement during classroom instruction. Conatively, students demonstrated active participation through collaborative discussions, interactive quizzes, and continuous interaction with the teacher and instructional media. These findings indicate that the instructional design implemented through Educaplay, which integrates visual representations, interactive quizzes, immediate feedback, and teacher facilitation, effectively fosters positive student responses during IPAS instruction.